Factors associated with knowledge about tuberculosis and attitudes of relatives of patients with the disease in Ribeirão Preto, São Paulo, Brazil - Isabela Moreira de Freitas; Marcela Paschoal Popolin; Michelle Mosna Touso; Mellina Yamamura; Ludmila Barbosa Bandeira Rodrigues; Marcelino Santos Neto; Juliane de Almeida Crispim; Ricardo Alexandre Arcêncio (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2015)
OBJECTIVE: To investigate the knowledge regarding tuberculosis among relatives of patients with tuberculosis and the possible factors associated with this event and also to conduct comparative analyses between groups of relatives with or with few knowledge regarding tuberculosis, considering their attitudes in both groups. METHODS: Cross-sectional study in which the sample was obtained through simple and randomized method. The data were collected by trained interviewers and validated tool. Logistic regression analyses were done using statistical software SPSS, version 22.0. RESULTS: Among the 110 subjects recruited for the study, 85 (87.5%) were women, and the mean age was 49 years. Regarding common symptoms of tuberculosis, 102 relatives (90.9%) pointed the chronic cough; regarding the knowledge about tuberculosis transmission modes, 100 (90.9%) of them pointed symptomatic respiratory as the probable infection source. The relatives also reported other tuberculosis transmission models: sharing of clothes (n = 87; 79.1%) and household utensils (n = 66; 60%); sexual relations (n = 50; 50%). Illiterate relatives (adjusted OR = 4.39; 95%CI 1.11 - 17.36), those who do not watch or watch little television (adjusted OR = 3.99; 95%CI 1.2 - 13.26), and also those who do not have the Internet access (adjusted OR = 5.01; 95%CI 1.29 - 19.38) were more likely to have low knowledge regarding tuberculosis. Regardless the group, with or without tuberculosis knowledge, the attitudes of both were satisfactory. CONCLUSION: There are evidences that social inequity is associated to the tuberculosis knowledge of patient relatives.